On sharing the benefits of communication - Efthymios Athanasiou; Santanu Dey; Giacomo Valletta (Fondazione Eni Enrico Mattei (FEEM), 2012)
We put forward a model of private goods with externalities. Agents derive benefit from communicating with each other. In order to communicate they need to have a language in common. Learning languages is costly. In this setting no individually rational and feasible Groves mechanism exists. We characterize the best-in-class feasible Groves mechanism and the best-in-class individually rational Groves mechanism.
Keywords: D70; D62; C60; 330; Groves Mechanisms; Externality; Budget Surplus or Deficit; Pareto Undominated